Smart Blind Stick - Shamsuddin, Nuratiqah; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2021)
Blindness is a medical term that refers to the state of being completely blind in both eyes. However, the term blindness is frequently used in a relative sense to refer to visual impairment or low vision. The conventional blind stick assists the blind, as well as visually impaired persons, in recognise the dangers of falling. However, many difficulties can occur in connection with the environmental awareness of the blind. This project will focus more on the problems on the pathway, such as drain, object on path and hanging object. Thus, the Smart Blind Stick enables blind people to communicate effectively with the environment in everyday work situations. This project aims to identify obstacles in front of the user using ultrasonic sensor, track the user’s location using GPS, and send location or emergency messages to guardians using GSM. It also focuses on aspects that provide cost-effective and efficient navigational help. This system has ultrasonic sensors HC-SR05, microcontrollers, GPS NEO6MV2 and SIM900 GSM. The system consists of two different parts: a slave transmitter and a master receiver. The sensor component identifies obstacles such as hanging objects, object on path, and drains, while the GPS module determines the location of the user and sends them to the guardian through message. The output of this project is a buzzer as the first warning and audio as the second warning for obstacles detection and an emergency message to the guardian. For the buzzer, the triggered distance for the drain is 90 cm to 120 cm, object on path from 150 cm to 200 cm, and hanging object is 140 cm to 180 cm. Below these distances for each obstacle, the audio will be given to the user as the second warning. To summarise, the purpose of this project is to achieve all of the previously stated objectives. This project can be improved by using Blynk programmed, which can turn the Smart Blind Stick into an IoT project and add a vibrator for further convenience and versatility.